Reducing the risks of nuclear war-the role of health professionals - Kamran Abbasi; Parveen Ali; Virginia Barbour; Kirsten Bibbins-Domingo; Marcel G M Olde Rikkert; Andy Haines; Ira Helfand; Richard Horton; Bob Mash; Arun Mitra; Carlos Monteiro; Elena N Naumova; et al. (Ntec Specialist, 2023)
In 2007, the IPPNW launched the International Campaign to Abolish Nuclear Weapons, which grew into a global civil society campaign with hundreds of partner organisations. A pathway to nuclear abolition was created with the adoption of the Treaty on the Prohibition of Nuclear Weapons in 2017, for which the International Campaign to Abolish Nuclear Weapons was awarded the 2017 Nobel Peace Prize. International medical organisations, including the International Committee of the Red Cross, the IPPNW, the World Medical .Association, the World Federation of Public Health Associations, and the International